Process design of oxidation pond and package treatment plant (ITM Shah Alam) / Mohd Shafri Abdul Aziz - Abdul Aziz, Mohd Shafri (1991)
In the design of biological treatment plant, the importance of utilising the bacteria, cannot be over emphasized. Many results found outside this country are not really applicable in local situations, for example, the effect of temperature and the nature of wastewater are different in different environments. Furthermore, most of this data are obtained either empirically, based on pilot plant and prototype treatments plants. This study wi11 of help to determine the local process parameters, for example decay rate, flow characteristics and other relevant process design parameters.